Rapid weight loss and combat athletes: a study on psychological resilience and mechanical hyperalgesia - Çaglar, E. Ç.; Ceylan, L.; Ermis, S. A.; Çamiçi, F.; Eliöz, M.; Uzun, R. N.; Çiçek, G.; Kusan, M.; Bayraktar, M. T.; Sahin, F. N.; Küçük, H. (Frontiers in Psychology, 2025)
Introduction: The study investigates the effects of Rapid Weight Loss (RWL) on the levels of psychological resilience and mechanical pain sensitivity in elite kickboxers. The primary aim was to examine changes in psychological resilience subdimensions and pressure pain threshold (PPT) values in the thoracolumbar region before and after a one-month RWL period leading up to competition. Hypotheses included expectations of significant reductions in PPT values due to biomechanical and physiological changes during RWL, along with improvements in psychological resilience subdimensions due to structured routines and social support.